Reduced expression of FOXE1 in differentiated thyroid cancer, the contribution of CPG methylation, and their clinical relevance - De Lima, Erika Urbano; Dos Santos, Filipe Ferreira; Da Silva, Igor Campos; De Lima, Cláudio Rogério Alves; Frutuoso, Vitoria Sousa; Caso, Gustavo Felisola; De Oliveira, Paloma Ramos; Bezerra, Ana Karina; Cerutti, Janete Maria; Tamura, Rodrigo Esaki; Ramos, Helton Estrela; Rubio, Ileana Gabriela Sanchez de (Frontiers in Endocrinology, 2024)
Introduction: Forkhead box E1 (FOXE1) is a transcription factor with a crucial role in thyroid morphogenesis and differentiation. Promoter hypermethylation downregulated FOXE1 expression in different tumor types; nevertheless, its expression and relation with the methylation status in differentiated thyroid cancer (DTC) remain unclear.Methods: A total of 33 pairs of PTC tumors and non-tumors matched samples were included.Tumor cell cultures were treated with either 5-Aza-2′-deoxycytidine demethylating agent or DMSO. RT-PCR and western blotting were performed to assess FOXE1 expression. The methylation status was quantified by bisulfite sequencing. Luciferase gene assay was used to determine CPG-island functionality. Gene expression and promoter methylation of FOXE1 and FOXE1-regulated genes were also analyzed with data from The Cancer Genome Atlas (TCGA) thyroid samples.Results: After demethylating treatment, increased FOXE1 mRNA was observed concomitantly with reduced promoter methylation of CpGisland2. Negative correlation between mRNA downregulation and increased methylation level of CpGisland2 was observed in tumors.Diminished protein expression was also detected in some DTC cell lines and in some tumor samples suggesting the involvement of post transcriptional regulatory mechanisms.CPGisland2 was proved to be an enhancer. TCGA data analysis showed low FOXE1 mRNA expression in tumors with negative correlation with methylation status and positive correlation with the expression of most of its target genes. FOXE1 reduced expression accompanied by a high methylation level was associated with PTC aggressiveness (tall cell variant, advanced extra thyroid extension, T4 AJCC classification), age at diagnosis (over 45 years old), and presence of BRAFV600E mutation. Conclusion: FOXE1 mRNA was downregulated in DTC compared with non-tumors, followed by high CpGisland methylation. Coupling of low mRNA expression and high methylation status was related to characteristics of aggressiveness of DTC tumors.